Prevalence of Weight Cycling and its Relation to Health Indicators in Finland - Marjaana Lahti‐Koski; Satu Männistö; P Pietinen; Erkki Vartiainen (2005)
Abstract Objective : This study was performed to identify weight cyclers and to assess the prevalence of weight cycling and its relation to health indicators in Finnish adults. Research Methods and Procedures : Data for the study consisted of 3320 men and 3540 women (25 to 64 years of age). The subjects went through a health examination, and data on intentional weight losses and regains during the last 10 years were collected by a questionnaire. The subjects were divided into five groups: severe weight cyclers (weight loss ≥ 5 kg at least three times with regain), mild weight cyclers (weight loss ≥ 5 kg one to two times and regain), successful dieters (weight loss ≥ 5 kg with no regain), nonobese nondieters, and obese nondieters. Results : Approximately 7% of men and 10% of women were defined as severe weight cyclers, and an additional 11% and 19% were defined as mild weight cyclers, respectively. In men, 20% of severe weight cyclers and 15% of obese nondieters perceived their health as poor, whereas in other groups, these proportions were <10%. In both sexes, severe weight cyclers seemed to have visited a doctor more frequently than nonobese nondieters. Severe weight cyclers were also more likely to use some medication compared with other groups. Discussion : Weight cycling is more common in women than in men, and it seems to be associated with more regular visits to a doctor and poor self‐perceived health. However, because of the cross‐sectional design of the study, causal conclusions cannot be drawn.